The mediating effects of an adult reading program on orders of mind and decision-making three case studies - Kim, Yong-Chan (2008)
This research is a case study of an adult functional literacy program for the employees of Kimbel Internarional, a manufacturing and retailing company of ladies' bags. The study adopted a longitudal content area reading program that would lead adult learners to higher concept development and eventually result in mature decision-making. Classes were held for seven students over a three-year period with the main objectives of improving reading comprehension, oral communication, and critical thinking. Afterwards, three participants were chosen to observe how they would act without any enforcement from the researcher. The program had different effects on the participants but these effects were not literacy effects but rather mediated ones. The effect of the Reading Program is largely dependent on the meaning of literacy in the lives of the students, and is influenced by both the system (norms) and the environment (values) in which he is exposed to.